By the Bank: A Reflection on the Riverbanks and Love Letters to the Rio Doce - Cirillo, José (Farol, 2025)
This text discusses the impact of the 2015 Samarco dam collapse (MG) on the Rio Doce, highlighting the environmental and social devastation resulting from contamination by mining waste. The riverside landscape, once marked by affection and subsistence, has become a diseased ecosystem, rendering traditional activities unviable and contaminating water resources. It also addresses the artistic project "Monuments of Love to the Rio Doce" (2018-2020), led by Piatan Lube, who collected letters from affected communities in Espírito Santo. The initiative uses art as activism to denounce environmental crime and recover collective memories, redefining the relationship between culture, nature, and resistance.
Keywords: Mariana disaster; environmental contamination; engaged art; Rio Doce; collective memory